Determination of Orellanine in Human Biological Matrices Using Liquid Chromatography with High-Resolution Mass Spectrometry Detection: A Validated Method Applied to Suspected Poisoning Cases. Issue 1 (16th March 2022) - Flament, Estelle; Guitton, Jérôme; Gicquel, Thomas; Paret, Nathalie; Jarrier, Nathalie; Creusat, Gaelle; Tournoud, Christine; Labadie, Magali; Gaulier, Jean-Michel; Gaillard, Yvan
Abstract: Consumption of mushrooms can become unsafe for the consumer in case of confusion. Some fungi of Cortinarius genus contain the nephrotoxic mycotoxin orellanine responsible for their toxicity. Related case poisoning diagnosis is a challenge for both clinicians and analysts because of a long latency period between intake and toxic syndrome, the lack of available information in literature and the numerous pitfalls of orellanine identification/quantification in biological samples. In this situation, we propose an analytical method designed for the orellanine detection and/or quantification in biological matrices such as plasma, urine and whole blood, in a context of related intoxication suspected case. Using 1 mL biological sample volume, this liquid chromatographic with high-resolution mass spectrometry detection method (i) exhibits a limit of quantification for orellanine of 0.5 µg/L in plasma and urine and (ii) enables orellanine detection in whole blood with a limit of detection of 0.5 µg/L. This validated analytical method was successfully applied to 10 suspected intoxication cases.